2022
DOI: 10.1029/2022gl098041
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne Evidence That Ice‐Nucleating Particles Influence High‐Latitude Cloud Phase

Abstract: Mixed‐phase clouds (MPCs), which consist of both supercooled cloud droplets and ice crystals, play an important role in the Earth's radiative energy budget and hydrological cycle. In particular, the fraction of ice crystals in MPCs determines their radiative effects, precipitation formation and lifetime. In order for ice crystals to form in MPCs, ice‐nucleating particles (INPs) are required. However, a large‐scale relationship between INPs and ice initiation in clouds has yet to be observed. By analyzing satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 93 publications
1
6
0
Order By: Relevance
“…Figure 2 (c) underlines the differences in this initial development by emphasising the initial relative lack of mixed-phase clouds early in MCAO (the gradient highlighted as Region A). This gradient in the temperature at which mixed-phase clouds become the majority has previously been observed by Carlsen and David (2022), who found that the temperature at which a cloud regime switched from being liquid-dominant to mixed-phase dominant (which they called T*) increased as a function of distance from the ice edge, until a plateau is reached at about -15°C. They also observed a seasonal dependence; during the summer, there was a slightly weaker gradient in T* from the ice edge (from about -17°C to -15°C) than in the winter (from about -22°C to about -15°C).…”
Section: Cloud Propertiessupporting
confidence: 71%
“…Figure 2 (c) underlines the differences in this initial development by emphasising the initial relative lack of mixed-phase clouds early in MCAO (the gradient highlighted as Region A). This gradient in the temperature at which mixed-phase clouds become the majority has previously been observed by Carlsen and David (2022), who found that the temperature at which a cloud regime switched from being liquid-dominant to mixed-phase dominant (which they called T*) increased as a function of distance from the ice edge, until a plateau is reached at about -15°C. They also observed a seasonal dependence; during the summer, there was a slightly weaker gradient in T* from the ice edge (from about -17°C to -15°C) than in the winter (from about -22°C to about -15°C).…”
Section: Cloud Propertiessupporting
confidence: 71%
“…The sharp gradient in I in the vicinity of the Antarctic Polar Front (APF; 50–55°S; Freeman & Lovenduski, 2016) is consistent with the previous finding that mixed‐phase clouds become increasingly scarce poleward of that point (Mace et al., 2020, 2021). The causes of low heterogeneity to the south of the APF are likely complex, as changes in sea surface temperature and sea ice coverage are known to have myriad effects on boundary layer clouds (e.g., Carlsen & David, 2022; Eirund et al., 2019; Sotiropoulou et al., 2016; Young et al., 2017). Low I over the SO is also consistent with the fact that, in some models, biases in LCF and absorbed shortwave radiation are larger over the SO than in the extratropical NH (Kay et al., 2016; Tan et al., 2016; Trenberth & Fasullo, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The spring and summertime maximum in I seen throughout the extratropics is broadly consistent with the idea that INP availability affects phase heterogeneity. Several field‐based studies have found that INP concentrations in the Arctic surge after the springtime thaw of sea ice and land‐based snow (Creamean et al., 2018; Tobo et al., 2019; Wex et al., 2019), and these seasonal fluctuations were recently found to affect cloud glaciation temperatures (Carlsen & David, 2022). In the SO region, I is elevated during the ice‐free time of the year and depressed during the ice‐covered seasons, suggesting that INPs may enhance heterogeneity there.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we reduce the amount of INPs available across all simulations by a factor of 10 3 (INP factor: 0.001). Observational studies show that INPs are important for controlling cloud phase (Carlsen & David, 2022;Creamean et al, 2022;Sze et al, 2023) and that climate models overestimate the amount of activated INPs in regions with the most frequent MPCs. This is especially pronounced over the Southern Ocean and the Arctic, where model INP concentration can be orders of magnitude too high (Vergara-Temprado et al, 2018;Vignon et al, 2021;Li et al, 2022).…”
Section: Implementation Of Observational Constraints In Noresm2mentioning
confidence: 99%